Physical Assessment Skills Used by Registered Nurses (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2021)
Background: Nurses work in a wide variety of settings. Therefore, it is essential for nursing educators to continually evaluate and adapt nursing programs to ensure that the curricula prepare students to practice in a variety of health care settings. In this study, we sought to determine which skills were routinely used by registered nurses and to examine whether the cumulative number of practice settings influenced the number, and type, of physical assessments used.Methods: An electronic or a paper survey was distributed to registered nurses who worked as nursing clinical instructors at a mid-sized university in this cross-sectional study. Measures of frequency and central tendency described participant characteristics and physical assessment skills. A Kruskal-Wallis test was used to investigate an association between the number of practice settings and physical assessment skills used.Results: Forty-nine surveys were completed (59.8% return rate), with 47 surveys used for inferential statistics. Practice settings ranged from one to six, with a median of two employment areas. Medical-surgical was the most common setting (65.3%). Respondents identified 25 physical assessment skills as being performed routinely in their clinical practice; 11 skills were routinely performed by 80% of respondents. The median number of core skills routinely performed in clinical practice was not statistically significant (x2 = 4.03; p = .25).Conclusion:  Academic and clinical nursing educators, policy makers, and nursing managers can use this study’s findings to supplement decision-making concerning nursing employment and continuing education opportunities.